Losses never sleep – The effect of tax loss offset on stock market returns during economic crises - Reinald Koch; Svea Holtmann; Henning Giese (Journal of Business Economics, 2023)
We analyze to what extent more generous tax loss offset regulations are associated with a weaker decline and stronger recovery of firm stock prices during economic crises. We argue that an unrestricted loss carryforward and, particularly, an unrestricted loss carryback provides firms with additional liquidity, which should lower the risk of bankruptcy and can be used for investment purposes. Our empirical findings document that (1) an unrestricted loss carryforward and an unrestricted loss carryback result in a weaker decline and more timely recovery of stock prices during the considered crises, (2) this effect is stronger in high-tax countries, and (3) this effect is also dependent upon pre-crisis profitability.
Keywords: H25; G01; 650; Tax loss offset; Economic crisis; Firm performance